1989
DOI: 10.1007/bf00974601
|View full text |Cite
|
Sign up to set email alerts
|

Combat addiction: Overview of implications in symptom maintenance and treatment planning

Abstract: T o m b a t addiction" is discussed as a concept central to understanding the chronicity and treatment-resistant quality of post-traumatic stress disorder in Vietnam combat survivors. Possible neurophysiologic, neurochemical, neuroelectrical, and behavioral parameters are addressed with regard to these mutually rein forcing excitatory states beginning with multiple combat experiences. Interviews with 100 such veterans revealed the remarkably frequent (94%) description of intrusive realistic reexperiencing of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…An outline of findings has been published elsewhere (Solursh, 1989). These veterans averaged age 40.5 years in 1987.…”
Section: Our Experiencementioning
confidence: 99%
“…An outline of findings has been published elsewhere (Solursh, 1989). These veterans averaged age 40.5 years in 1987.…”
Section: Our Experiencementioning
confidence: 99%
“…Both PTSD and personality disorders involve behaviors and symptoms that are pervasive across a variety of situations and are persistent over an extended period of time. Empirical studies have shown each of these disorders, when they occur individually, to be particularly intractable (Green, Lindy, Grace, &Leonard, 1992;Herman, 1992;Long et al, 1989;Solursh, 1989). When these disorders co-occur in a single individual, as is often the case for combat veterans, associated symptoms appear to be more highly treatmentresistant (Breslau & Davis, 1992).…”
mentioning
confidence: 99%
“…Solursh (1989), in a study of 100 war veterans suffering from PTSD, reported explosive aggression to be present in 97% of his sample. Collins and Bailey (1990), in a sample of 1140 prisoners, found that those suffering from PTSD, or symptoms associated with the disorder, were more likely to commit explosive forms of violence.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 94%